The Stationary Distribution of Returns and Portfolio Separation in Capital Markets: A Fundamental Contradiction - Rosenberg, Barr; Ohlson, James A. (Journal of Financial and Quantitative Analysis, 1976)
Barr Rosenberg, James A. Ohlson, The Stationary Distribution of Returns and Portfolio Separation in Capital Markets: A Fundamental Contradiction, The Journal of Financial and Quantitative Analysis, Vol. 11, No. 3 (Sep., 1976), pp. 393-402